CALENDAR. (Computer (00189162), 2009)
The article presents a calendar of events for 2009 including a VLSI test symposium in Santa Cruz, California in May, a symposium on computer arithmetic in Portland, Oregon in June, and a conference on Web services in Los Angeles, California in July.